2001
DOI: 10.1590/s1516-35982001000500021
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da utilização de oligossacarídeo manose e acidificantes sobre o desempenho de coelhos em crescimento

Abstract: Foi conduzido um experimento com o objetivo de se determinar os efeitos da adição às rações de ácido fumárico, Oligossacarídeo manose (BIO-MOS®), acidificante (ACID-ALL®) e a combinação de oligossacarídeo com acidificantes sobre o desempenho de coelhos em crescimento. Foram utilizados 100 coelhos da raça Nova Zelândia Branco, 50 machos e 50 fêmeas, de 39 a 75 dias de idade, distribuídos em um delineamento experimental inteiramente casualizado com cinco tratamentos e 10 repetições e dois animais por unidade exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 4 publications
0
9
0
8
Order By: Relevance
“…On the other hand, Hullar et al (1996) obtained improvements in rabbits' performance after adding sodium butyrate to the diet for 4 wk. Dissenting results have also appeared with the addition of other acids: fumaric acid led to a improvement in the performance parameters of growing and fattening rabbits although not statistically significant (Scapinello et al, 2001;Michelan et al, 2002) and formic acid together with lactic acid improved the feed efficiency and average daily weight gain in 30-55 and 56-84 d old rabbits (Cesari et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Hullar et al (1996) obtained improvements in rabbits' performance after adding sodium butyrate to the diet for 4 wk. Dissenting results have also appeared with the addition of other acids: fumaric acid led to a improvement in the performance parameters of growing and fattening rabbits although not statistically significant (Scapinello et al, 2001;Michelan et al, 2002) and formic acid together with lactic acid improved the feed efficiency and average daily weight gain in 30-55 and 56-84 d old rabbits (Cesari et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Brazilian researchers (Scapinello et al, 2001;Michelan et al, 2002) found that the inclusion of 1,5% of fumaric acid in the feeds of growing rabbits tended to improve both the daily gain and the feed efficiency, but the differences were not statistically significant. Similar results were reported by Hollister et al (1990) (Table 5).…”
Section: Organic Acid For Rabbitsmentioning
confidence: 99%
“…Combining organic acids with prebiotics (Scapinello et al, 2001) or with probiotics (Michelan et al, 2002) did not significantly improve performances, though mortality was significantly reduced in one trial (Hollister et al, 1990) where fumaric acid was combined with Lacto-Sacc.…”
Section: Organic Acid For Rabbitsmentioning
confidence: 99%
“…Contudo, ainda não é conhecida à composição microbiana ideal de um produto probiótico, mas a eficiência do seu uso é estritamente dependente da quantidade e das características das cepas bacterianas utilizadas na elaboração do aditivo alimentar SCAPINELLO et al, 2001). Os mananoligossacarídeos são derivados da parede celular interna de leveduras e seu modo de ação é ligando-se a certas bactérias patogênicas no ambiente gastrintestinal, essas bactérias ligadas aos oligossacarídeos não podem aderir à infecção iniciada no intestino (DE ARAÚJO et al, 2007), também auxiliam na preparação do sistema imune para combate de infecção (SCAPINELLO et al, 2001).…”
Section: Modo De Ação Local De Atuação Efeitos Diretos Efeitos Indiretosunclassified
“…Os mananoligossacarídeos são derivados da parede celular interna de leveduras e seu modo de ação é ligando-se a certas bactérias patogênicas no ambiente gastrintestinal, essas bactérias ligadas aos oligossacarídeos não podem aderir à infecção iniciada no intestino (DE ARAÚJO et al, 2007), também auxiliam na preparação do sistema imune para combate de infecção (SCAPINELLO et al, 2001).…”
Section: Modo De Ação Local De Atuação Efeitos Diretos Efeitos Indiretosunclassified